Memikirkan Kembali Dimensi Kelembagaan PDAM dalam Penyediaan Air Bersih di Kota Dumai - Isril Isril; Zulfa Harirah MS; Annas Rizaldi (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2022)
The scarcity of clean water in Dumai City has been going on for decades. PDAM Tirta Dumai Bersemai is required to have good performance so that the distribution of clean water is evenly distributed to all people. However, PDAM faces many challenges in achieving this goal. Challenges in the form of limited funds, human resources, and influential environmental factors so that performance is said to be not optimal. PDAM almost went bankrupt in 2016, trying to get up in 2018-2020 by making various efforts. This paper is intended to explain the success of PDAM in providing clean water. Success is interpreted not as an equal supply of clean water to all people but rather as success in getting through a period of bankruptcy. This research was conducted using qualitative methods by collecting data through interviews and documentation. The field results were then analyzed, resulting in the following findings. First, PDAM can be involved in various clean water supply schemes such as SPAM NUWS, PPP, and Durolis. This involvement shows the trust of the parties in the PDAM's performance. Second, improvements in PDAM performance are inseparable from improvements in PDAM's internal management. Improvement of PDAM's institutional dimension is the key to PDAM's revival. The leadership of the first and second periods of the principal director of PDAM showed significant changes. So that in the future, PDAM leadership must be based on qualified knowledge, information, and experience in managing clean water.